Moderating role of customer value on the effect of animosity, ethnocentrism and religiosity toward purchase decision: study on Chinese cosmetic - Asyhari Asyhari; Sitty Yuwalliatin (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
Purpose – This study aims to examine the moderating role of customer value on the relationship between animosity, ethnocentrism, and religiosity on purchasing decisions of Chinese brand cosmetics. Design/methodology/approach – This study used a quantitative research design. Selected 150 millennial in the city of Semarang as samples was taken using the purposive sampling technique. The data were analyzed using a moderated PLS-SEM. Findings – The results showed that hostility, ethnocentrism, and religiosity had a negative and significant effect on purchasing decisions. The study also found that customer value actually becomes a moderator that can weaken the relationship between these three variables on purchasing decisions. Research limitations/implications – Data were collected from millennial in the city of Semarang. This condition causes limitations as it may not capture reflections from other age groups that are different from the sample. Thus, further marketing studies are needed with comprehensive respondent characteristics, increasing the number of samples, and including other moderating variables such as the level of customer trust. Practical implications – The empirical findings of the current study help international businesses in understanding negative factors as antecedents of purchase decisions. This will be useful in planning marketing activities and efforts to increase market share. In addition, managers can consider the customer value to gain the trust of customers. Originality – The study on the negative influence of animosity, ethnocentrism, and religiosity on purchase decisions in Indonesia is very limited. This study focuses on explaining the importance of customer value as a moderating factor, in anticipation of the negative relationship. This study contributes to multinational companies understanding the consumer purchase decision.